Efektifitas Buku Saku Digital untuk Transformasi Pengetahuan dan Sikap Remaja Putri tentang Pencegahan Anemia: The Effectiveness of Digital Pocketbook for the Transformation of the Knowledge and Attitude of Adolescent Girls about the Prevention of Anemia - Nuryana, Hurip; Rachmawati, Emma; Khusun, Helda; Mulyawati, Devi Annisa; Lestari, Hesti (Amerta Nutrition, 2025)
Background: Anemia is a significant health issues among adolescent girls, negatively impacting their life cycle. Bogor City has an anemia prevalence of 28%. The Indonesian Ministry of Health has introduced a digital pocketbook "Prevention of Anemia for Pregnant Women and Adolescent Girls", an educational tool. Objectives: This study aimed to assess the effectiveness of the digital pocketbook in improving the knowledge and attitudes of adolescent girls about preventing anemia. Methods: This quasi-experiment study used Pretest-Posttest with Control Group design. Samples were purposively chosen from female students in four junior high schools in Bogor (40 students per group per school). Group 1 received Digital Pocket Book with Presentatio, Group 2 received Digital Pocket Book only, and Group 3 served as Control. Changes in knowledge and attitude scores before and after the intervention were analyzed using Wilcoxon test, while the difference among the three groups were tested using Kruskall-Wallis tests with post-hoc analysis (p-value<0.05). Results: Before the intervention, knowledge and attitudes score  was relatively homogeneous (p-value=0.068 and 0.695). After the intervention, Group 1 and 2 showed significant improvements compared to the control. Group 1's knowledge increased significantly (3.01 ± 3.613), followed by Group 2 (1.78 ± 2.947). Attitude improvement was also highest in Group 1 (5.10 ± 7.947), followed by Group 2 (2.65 ± 7.118). Additionally, 95% of respondents rated the digital pocketbook as excellent. Conclusions: The digital pocketbook iss considered effective and informative in improving the knowledge and attitudes of adolescent girls about preventing anemia, regardless of additional explanation.